GLYCAEMIA CONTROL THROUGH MODERATE AND HIGH INTENSITY ACUTE RESISTANCE TRAINING IN DIABETICS (Fiep Bulletin - online, 2014)
ntroduction: Diabetes is a world health problem and physical exercise can help at the treatment of it.Aim: The aim of this study was to evaluate if patients with diabetes mellitus type 2 (DM2) are able to reduce the blood glucose level after acute resistance training in high and moderate intensity. Methodology: A total of 20 male patients with DM2 were selected, 10 to each group, and with age between 54±8 years. One of the groups did the training protocol at a 60% (D-60) and the other at 75% (D-75) of the maximum load.Blood glucose was checked by capilaris using a glucose meter of the brand Accu-chek Active-Roche 30 minutes prior to the exercise protocol and right after the training. It was calculated the mean, standard deviation, standard error, and absolute delta to show the variance between before and after training. Kolmogorov-Smirnov was done to check the normality of the sample. Student T test was done. It was adopted p
Keywords: diabetes mellitus; blood glucose; resistance training.